Similarity and variability of blocked weather-regime dynamics in the Atlantic-European region - Teubler, Franziska; Riemer, Michael; Polster, Christopher; Grams, Christian M.; Hauser, Seraphine; Wirth, Volkmar (2022)
Weather regimes govern an important part of the sub-seasonal variability of the mid-latitude circulation. Due to their role in weather extremes and atmospheric predictability, regimes that feature a blocking anticyclone are of particular interest. This study investigates the dynamics of these ''blocked'' regimes in the North Atlantic-European region from a year-round perspective. For a comprehensive diagnostic, we combine wave activity concepts and a piecewise potential-vorticity (PV) tendency framework. The latter essentially quantifies the well-established PV perspective of mid-latitude dynamics. All blocked regimes during the 1979–2021 period of ERA5 reanalysis are considered. Wave activity characteristics exhibit distinct differences between blocked regimes. After regime onset, one regime (Greenland Blocking) is associated with a suppression of wave activity flux, whereas two other regimes (Atlantic Ridge and European Blocking) are associated with a northward deflection of the flux without a clear net change. During onset, the envelope of Rossby wave activity retracts upstream for Greenland Blocking, whereas the envelope extends downstream for Atlantic Ridge and European Blocking. The fourth regime (Scandinavian Blocking) exhibits intermediate wave activity characteristics. From the perspective of piecewise PV tendencies projected onto the respective regime pattern, the dynamics that govern regime onset exhibit a large degree of similarity: Linear Rossby wave dynamics and nonlinear eddy PV fluxes dominate and are of approximately equal relative importance, whereas baroclinic coupling and divergent amplification make minor contributions. Most strikingly, all blocked regimes exhibit very similar (intra-regime) variability: a retrograde and an upstream pathway to regime onset. The retrograde pathway is dominated by nonlinear PV eddy fluxes, whereas the upstream pathway is dominated by linear Rossby wave dynamics. Importantly, there is a large degree of cancellation between the two pathways for some of the ...